Kontinuitas tradisi breast ironing dalam komunitas imigran Kamerun di Inggris - Simangunsong, Rahayu A. H. (Journal of Gender Equality Disability Social Inclusion and Children, 2024)
The practice of breast ironing is one of many traditions in the world whose practice is based on the mindset that women's sexuality is something that must be controlled. This paper is intended to answer the question that is central to the author's research, namely: "Why do African immigrant communities in the UK continue the tradition of breast ironing when it is so risky?" To understand the context underlying the beliefs and practices of African immigrant women in the UK, the author adopts the ideas of Black African Feminism (BAF) by A La Awa Thiam. BAF argues that the history of colonialism has influenced the reinforcement of patriarchal ideologies and gender dynamics in Africa. BAF seeks to raise issues related to family life such as domestic violence, FGM, early marriage, polygamy, women's reproductive rights, women's inheritance rights, and HIV/AIDS. The continuity of the breast ironing tradition in the Cameroonian immigrant community in the UK is influenced by the socio-cultural context embedded in the community and the unsuccessful cultural adaptation that occurs between the minority community (Cameroonian immigrants) and the dominant community (local community). The efforts that can be made to stop this tradition are to build awareness within the community itself, in this case, the role of civil society organizations and NGOs is crucial.